Management in Perspective Automation: Our Greatest Asset—Our Greatest Problem? - Megginson, Leon C. (Academy of Management Journal, 1963)
The article discusses the impact of automation on U.S. business enterprises in 1963. There are two divergent schools of thought in the U.S. regarding automation. One group believes that automation ...